Fundamental study of shear controllable synthesis of fine particles using taylor-couette flow reactor - Liu, Lu (2021)
Fine particles generally have special physicochemical properties, such as good solubility, dispersibility, and adsorption due to their extremely large specific surface area. With such advantages, they have been attracting wide attention in the fields of pharmaceuticals, catalyst, food, cosmetics, chemicals and electronics. Among various methods to prepare fine particle materials, reactive precipitation presents its advantages in terms of simple configuration, flexible operation, and low cost.